Role of a human factor in road traffic safety - Mygal, Galina; Protasenko, Olga (Видавництво Львівської політехніки, 2018)
The problem of influence of a human factor on road traffic safety is considered. It is shown that the studying of psychological and psycho-physiological characteristics of human as an integral part of the system "driver-car-road-environment" is needed for optimization of road transport environment and decreasing of risks caused by the human factor.
Роль людського чиннику у безпеці дорожнього руху
Keywords: 656.11(083.74)